2019
DOI: 10.1037/aca0000147
|View full text |Cite
|
Sign up to set email alerts
|

More than skin deep: Judgments of individuals with facial disfigurement.

Abstract: People's physical appearance can have a profound impact on their social interactions. Faces are often the first thing we notice about people and the basis on which we form our first impressions of them. People with facial disfigurement are discriminated against throughout their lives. Currently, we do not know why this discrimination occurs. In order to develop viable interventions, we must first understand the nature of people's reactions to disfigurement. In this work, we tested the hypothesis that a "disfig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
65
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(74 citation statements)
references
References 46 publications
4
65
4
1
Order By: Relevance
“…5 Attractive people are seen as more trustworthy, socially competent, dominant, better adjusted, more capable in school and work, and also receive greater rewards and lesser punishments than their average looking peers. [5][6][7] Adults and children ascribe desirable personality traits to attractive faces of adults and children and discriminate against unattractive faces even if they are friends and family members. 5 Attractiveness and trustworthiness judgments are consistent across cultures 5 and are made extremely quickly.…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Attractive people are seen as more trustworthy, socially competent, dominant, better adjusted, more capable in school and work, and also receive greater rewards and lesser punishments than their average looking peers. [5][6][7] Adults and children ascribe desirable personality traits to attractive faces of adults and children and discriminate against unattractive faces even if they are friends and family members. 5 Attractiveness and trustworthiness judgments are consistent across cultures 5 and are made extremely quickly.…”
Section: Mainmentioning
confidence: 99%
“…6 People with facial disfigurements are not only perceived as less attractive and less likely to be selected as romantic partners, they are also thought of as having unfavourable personality traits (e.g., lack of emotional stability, conscientiousness), internal attributes (e.g., unhappiness, lower intelligence), social qualities (e.g., untrustworthiness, unpopularity) 6,7,9,10 and are treated poorly in social interactions. 6,9,[18][19][20][21][10][11][12][13][14][15][16][17] In popular culture, facial disfigurement is often used to distinguish good and evil characters. 22 Well known examples of disfigured villains are Alice in a Wonderland (Macrocephaly).…”
Section: Mainmentioning
confidence: 99%
“…‘Beauty is good’ and ‘disfigurement is bad’ stereotypes are widespread and may be innate . Children with facial differences and their parents report higher levels of perceived stigmatisation than their peers .…”
Section: ‘Disfigurement Is Bad’mentioning
confidence: 99%
“…A similar study with adult reviewers and images of adult patients before and after surgical correction of facial differences found that ‘Posttreatment individuals were judged as having more positive internal attributes: They were rated as nicer, more honest, happier, and calmer than pretreatment individuals. They were also rated as more intelligent, competent, and hardworking’ …”
Section: ‘Disfigurement Is Bad’mentioning
confidence: 99%
“…In the pre-treatment phase, they were considered less sociable and happy, less dominant, emotionally unstable, and tended to be viewed more as objects of curiosity than others. According to Jamrozik, et al (2019), these results suggest that the negative stereotype of people with a facial disfigurement can lead to discrimination in multiple socio-cultural contexts that lead to loss of quality of life. Losee, Fletcher, and Gorantlia (2012) and Wang et al (2018) sate that facial deformity can cause significant interact socially (Rumsey & Harcourt, 2004).…”
mentioning
confidence: 99%